Reasons why self-directed learning is important in South African during the COVID-19 pandemic - Mahlaba, S.C. (South African Journal of Higher Education, 2020)
We live in unprecedented times and are bombarded with various changes to normality and everyday usual business. Recently, the COVID-19 pandemic has changed the face of university education in South Africa and the world. The move towards remote teaching has denied medical students to do their practical work in hospitals, science students to access their laboratories where they conduct their experiments as part of their coursework and has denied students a chance to gain information in university libraries. This has had effects on both students’ and lecturers’ progress in the academic year and has called for an abrupt change in the way they view teaching and learning. The aim of this article is to highlight the significance of being a self-directed learner during the COVID-19 pandemic and to answer the following question: Why is self-directed learning important in South Africa during the COVID-19 pandemic? To answer this question, I discuss the challenges faced globally during the COVID-19 pandemic, and I focus on the challenges higher education institutions face with regard to remote teaching. Thereafter, I discuss self-directed learning and its importance in students and teachers with the aim of highlighting what self-directed learners can do when faced with the abrupt changes brought about by COVID-19. Lastly, recommendations are made to highlight that higher education institutions should prepare learners to be self-directed in their learning in order to prepare them for such abrupt changes in the future.